A Wirelessly Controlled Smart Bandage with 3D‐Printed Miniaturized Needle Arrays. (13th February 2020) - Derakhshandeh, Hossein; Aghabaglou, Fariba; McCarthy, Alec; Mostafavi, Azadeh; Wiseman, Chris; Bonick, Zack; Ghanavati, Ian; Harris, Seth; Kreikemeier‐Bower, Craig; Moosavi Basri, Seyed Masoud; Rosenbohm, Jordan; Yang, Ruiguo; et al.
Abstract: Chronic wounds are one of the most devastating complications of diabetes and are the leading cause of nontraumatic limb amputation. Despite the progress in identifying factors and promising in vitro results for the treatment of chronic wounds, their clinical translation is limited. Given the range of disruptive processes necessary for wound healing, different pharmacological agents are needed at different stages of tissue regeneration. This requires the development of wearable devices that can deliver agents to critical layers of the wound bed in a minimally invasive fashion. Here, for the first time, a programmable platform is engineered that is capable of actively delivering a variety of drugs with independent temporal profiles through miniaturized needles into deeper layers of the wound bed. The delivery of vascular endothelial growth factor (VEGF) through the miniaturized needle arrays demonstrates that, in addition to the selection of suitable therapeutics, the delivery method and their spatial distribution within the wound bed is equally important. Administration of VEGF to chronic dermal wounds of diabetic mice using the programmable platform shows a significant increase in wound closure, re‐epithelialization, angiogenesis, and hair growth when compared to standard topical delivery of therapeutics. Abstract : A wirelessly controlled bandage with integrated 3D‐printed miniaturized needle arrays facilitates the delivery of different drugs with precisely controlled independent rates. The bandage significantly improves the healing of diabetic wounds.